Ultrasonography, Cytology, and Thyroglobulin Measurement Results of Cervical Nodal Metastasis in Patients With Unclear Papillary Thyroid Carcinoma - Lim, Jong Heon; Kim, Dong Wook; Park, Jin Young; Lee, Yoo Jin; Park, Ha Kyoung; Ha, Tae Kwun; Kim, Do Hun; Jung, Soo Jin; Park, Ji Sun; Moon, Sung Ho; Ahn, Ki Jung; Baek, Hye Jin (Frontiers in Endocrinology, 2019)
Objective: This study aimed to evaluate the ultrasonography (US), cytology, and thyroglobulin (Tg) measurement results of nodal metastasis in patients showing unclear US or cytology results of primary papillary thyroid carcinoma (PTC). Methods: From January 2016 to December 2018, 179 patients underwent US-guided fine-needle aspiration (FNA) to diagnose lymphadenopathy in the neck. Among them, 36 patients underwent subsequent total thyroidectomy and nodal dissection, and cervical lymph node (LN) metastasis from PTC was confirmed. However, 2 patients were excluded because of mismatch between the US and pathological findings of LNs. US images and cytological slides for metastatic LNs were retrospectively analyzed, and serum and FNA Tg levels for metastatic LNs were investigated using data from the electric medical records. Primary PTC patients with suspicious results on both US and cytology were classified as the clear group, and the remaining patients were classified as the unclear group. Results: Of the 34 patients, 24 had clear results of primary PTC on both US and cytology (clear group), whereas 10 had unclear results of primary PTC on US or cytology (unclear group). Of the 10 patients in the unclear group, 7 had suspicious nodal metastasis from PTC on cytology after US-guided FNA of the cervical LN, and the remaining 3 had negative cytology but a positive Tg measurement. Metastatic LNs with cystic change tended to show a positive Tg measurement but negative cytology. Conclusions: The combination of US, cytology, and Tg measurement is necessary for diagnosing nodal metastasis from PTC. In cases with unclear primary PTC on US or cytology, the detection of nodal metastasis may be helpful for assessing primary PTC.